Mathematical Modelling of Drug Transport and Uptake in a Realistic Model of Solid Tumour - Zhan, Wenbo; Gedroyc, Wladyslaw; Yun Xu, Xiao (Protein and Peptide Letters, 2014)
Effective delivery of therapeutic agents to tumour cells is essential to the success of most cancer treatment therapies except for surgery. The transport of drug in solid tumours involves multiple biophysical and biochemical proc- esses which are strongly dependent on the physicochemical properties of the drug and biological properties of the tumour. Owing to the complexities involved, mathematical models are playing an increasingly important role in identifying the factors leading to inadequate drug delivery to tumours. In this study, a computational model is developed which incorpo- rates real tumour geometry reconstructed from magnetic resonance images, drug transport through the tumour vasculature and interstitium, as well as drug uptake by tumour cells. The effectiveness of anticancer therapy is evaluated based on the percentage of survival tumour cells by directly solving the pharmacodynamics equation using predicted intracellular drug concentrations. Computational simulations are performed for the delivery of doxorubicin through different administration modes and doses. Our predictions show that continuous infusion is far more effective than bolus injection in maintaining high levels of intracellular drug concentration, thereby increasing drug uptake by tumour cells. On the other hand, bolus injection leads to higher extracellular concentration in both tumour and normal tissues compared to continuous infusion, which is undesirable as high drug concentration in normal tissues may increase the risk of associated side effects.
Keywords: prostate tumour